Designing Multimedia-Based E-learning to Support Learning of Faith and Morals, Especially in the Material on Praiseworthy Morals for Students - Rivaldi; Teguh Maulana Ihsan (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
Learning Aqidah Akhlak plays a crucial role in shaping students’ character, yet conventional lecture-based methods often fail to engage learners, making it difficult for moral values to be internalized effectively. Multimedia-based e-learning offers an innovative alternative as it presents moral content through visual elements, narration, and interactive activities that enhance students’ engagement. This study aims to examine the concept of multimedia-based e-learning, its relevance to the teaching of virtuous character, and the systematic steps required to design effective e-learning for character development. The method used is a literature review by analyzing books, national and international journals, as well as previous studies related to instructional multimedia and character education. The findings indicate that presenting moral values through multimedia can improve value comprehension, facilitate moral reflection, and encourage the application of positive attitudes when supported by the teacher’s role as a facilitator of values. The study concludes that designing multimedia-based e-learning can serve as an effective strategy in Aqidah Akhlak instruction, provided that it follows pedagogical principles and is complemented with continuous evaluation to ensure real behavioral change among students.